Analisis Skala Produksi UMKM Musae Chips Sebelum dan Sesudah Pembinaan Oleh KPw Bank Indonesia Jember - Masruroh, Amalia; Amalia, Hani Khairo; Widiastuti, Tika (Universitas Negeri Surabaya, 2024)
The MSME development program has become a key instrument in increasing consumer purchasing power, ultimately helping to mitigate monetary crises. Bank Indonesia plays a role as the monetary authority, with the Social Program of Bank Indonesia (PSBI) serving as an expression of empathy in addressing socio-economic issues. The KPw Bank Indonesia is also involved in MSME development programs, including the Musae Chips banana chips MSME in Jember. This study aims to: Understand the development process by KPw Bank Indonesia Jember for Musae Chips MSME, and Compare the production scale before and after the development program. The research employs a qualitative approach with a descriptive method, conducted at KPw Bank Indonesia Jember and Musae Chips MSME in Bangsalsari, Jember. Data collection techniques include observation, interviews, and documentation, with descriptive analysis and data validation through source triangulation. The results show that the development process focuses on enhancing MSME skills through training in various areas, including management, production, financing, and marketing, as well as organizing exhibitions to expand market reach. The production scale of Musae Chips MSME increased after the development program, but input costs also rose, affecting the product's pricing. The implications of these results indicate that the training successfully improved the skills and production scale of Musae Chips' MSMEs, which has the potential to expand market reach. However, the increase in input costs after the training may affect product prices, requiring a competitive pricing strategy to remain attractive to consumers.